UNDERSTANDING TEACHING APPROACHES FOR INFANTS AND TODDLERS IN MALAYSIAN TASKA: A QUALITATIVE CASE STUDY ON PARENTAL ASPIRATIONS - INTAN DAHWARNA ISMAIL; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study aims to examine the implementation of teaching and learning strategies in Child Care Centres (TASKA) to support the holistic development of infants and young children and meet the expectations of modern parents. In Malaysia, the National PERMATA Curriculum emphasizes education through play, inquiry and interaction. However, educators face challenges in balancing curriculum objectives with practices that are appropriate for children’s development due to changing parental aspirations that demand early exposure to literacy, numeracy and socio-emotional skills. This study uses a qualitative approach through library research and teacher interviews to identify strategies used in TASKA. Findings show that play-based approaches, sensory and interactive activities are often used. Teachers emphasize the importance of positive teacher-student relationships, effective communication with parents and continuous monitoring of children’s development. Continuous professional training and close collaboration are recommended to improve the quality of early childhood education in Malaysia.